Long-Term Toxicity Study of Topical Administration of a Highly-Stable rh-aFGF Carbomer 940 Hydrogel in a Rabbit Skin Wound Model - Li Zhang; Li Zhang; Li Zhang; Tongzhou Huang; Tongzhou Huang; Jianing Bi; Jianing Bi; Yingying Zheng; Yingying Zheng; Chao Lu; Chao Lu; Qi Hui; et al. (Frontiers Media S.A., 2020)
We developed a highly stable recombinant human acidic fibroblast growth factor (rh-aFGF) carbomer 940 hydrogel for wound healing. This study aimed to reveal toxicity target organs and the toxicity dose-response in the long-term administration of rh-aFGF carbomer 940 hydrogel in a rabbit skin wound model. New Zealand rabbits were topically administrated rh-aFGF carbomer 940 hydrogel at a daily dose of 900 IU/cm2, 1,800 IU/cm2, and 3,600 IU/cm2 for 28 days. Lyophilized rh-aFGF agent was used as the positive control group. General behavior, serum chemistry, skin irritation, immunogenicity, immunotoxicity, and histopathology were analyzed at designated time points. Results revealed that food intake, body weight, body temperature, heart rate, and eye examinations were all normal, suggesting no obvious toxicity induced by the rh-aFGF hydrogel. Medium and high dose rh-aFGF hydrogel groups and the positive control group displayed increased cell numbers in the local lymph nodes near the site of administration, likely caused mesenteric lymph node follicular hyperplasia, and this observation was alleviated after 14 days of recovery. Immunogenicity studies demonstrated that the serum antibody titer against rh-aFGF increased with the duration and number of drug applications but were not neutralization antibodies. After administration stopped, antibody titer decreased and disappeared in some mice. In summary, the safe dose for long-term administration of rh-aFGF carbomer 940 hydrogel for persistently damaged skin was 900 IU/cm2, which is 10 times that of the proposed clinical dosing.